Multimodal Monitoring in Large Hemispheric Infarction: Quantitative Electroencephalography Combined With Transcranial Doppler for Prognosis Prediction - Qi, Yajie; Xing, Yingqi; Wang, Lijuan; Zhang, Jie; Cao, Yanting; Liu, Li; Chen, Ying (Frontiers in Neurology, 2021)
Background: We aimed to explore whether transcranial Doppler (TCD) combined with quantitative electroencephalography (QEEG) can improve prognosis evaluation in patients with a large hemispheric infarction (LHI) and to establish an accurate prognosis prediction model. Methods: We prospectively assessed 90-day mortality in patients with LHI. Brain function was monitored using TCD-QEEG at the patient’s bedside. Results: Of the 59 (55.3 ± 10.6 years; 17 men) enrolled patients, 37 (67.3%) died within 90 days. Cox regression analyses revealed that a Glasgow Coma Scale (GCS) score ≤ 8 (hazard ratio [HR], 3.228; 95% confidence interval [CI], 1.335–7.801; P = 0.009), TCD-terminal internal carotid artery as the offending vessel (HR, 3.830; 95%CI, 1.301–11.271; P = 0.015), and QEEG-a (delta + theta)/(alpha + beta) ratio ≥ 3 (HR, 3.647; 95% CI, 1.170–11.373; P = 0.026) independently predicted survival duration. Combining these three factors yielded an area under the receiver operating characteristic curve of 0.905 and had better predictive accuracy than those of individual variables (P < 0.05). Conclusions: TCD and QEEG complement the GCS score to create a reliable multimodal method for monitoring prognosis in patients with LHI.